The role of the nitric oxide pathway in brain injury and its treatment--from bench to bedside. - Garry, P; Ezra, M; Rowland, M; Westbrook, J; Pattinson, K (Academic Press Inc., 2015)
Nitric oxide (NO) is a key signalling molecule in the regulation of cerebral blood flow. This review summarises current evidence regarding the role of NO in the regulation of cerebral blood flow at rest, under physiological conditions, and after brain injury, focusing on subarachnoid haemorrhage, traumatic brain injury, and ischaemic stroke and following cardiac arrest. We also review the role of NO in the response to hypoxic insult in the developing brain. NO depletion in ischaemic brain tissue plays a pivotal role in the development of subsequent morbidity and mortality through microcirculatory disturbance and disordered blood flow regulation. NO derived from endothelial nitric oxide synthase (eNOS) appears to have neuroprotective properties. However NO derived from inducible nitric oxide synthase (iNOS) may have neurotoxic effects. Cerebral NO donor agents, for example sodium nitrite, appear to replicate the effects of eNOS derived NO, and therefore have neuroprotective properties. This is true in both the adult and immature brain. We conclude that these agents should be further investigated as targeted pharmacotherapy to protect against secondary brain injury.